PENGARUH INOVASI PRODUK,HARGA,TEMPAT DAN PROMOSI DIGITAL TERHADAP PERILAKU KONSUMEN PADA KAWASAN LEMBU PUTIH DESA TARO - Putu Ratna Juwita Sari ,; Luh Kalpikha Putri Utami , (Juremi: Jurnal Riset Ekonomi, 2025)
In an increasingly competitive tourism industry, understanding consumer behavior is essential to attract and retain tourists. Consumer behavior covers a wide range of aspects, from natural beauty, culture, to the facilities and services offered. Tourism development, like other business developments, requires consideration of market tastes. To win the competition, tourist destinations need to understand how the various elements in the Marketing Mix, especially product, price, place, and promotion, affect their appeal to consumers. Quantitative research methods use numerical data and emphasize the research process on objective measurement of results using statistical analysis and are intended to determine whether there is a relationship between two or more variables. In addition, this study uses the help of a qualitative approach to describe the characteristics of respondents and the scale assessment given by respondents to all indicators in this study. An indicator is declared valid if it has a loading factor above 0.7 against the intended construct. In the model above, it can be seen that all indicators have a loading factor value above 0.7 which can be said to be valid. Prices that match product quality, Product quality is the main factor in forming positive perceptions of tourists towards tourist destinations. High-quality products can provide a satisfying experience and increase visitor loyalty. In the digital era, clear and complete information is very important to attract consumer attention. Digital promotions that provide useful information about products or services will increase tourists' interest in visiting. Accessibility is a factor that greatly influences tourists' decisions to visit the Lembu Putih tourist destination. Locations that are easy to reach will increase the number of visits, while locations that are difficult to reach can reduce tourist interest.